Social Media and Cyber-Crime Among Abraka Residents, Delta State, Nigeria - Agbaka, Joyce (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2024)
Social media platforms have become a routine for many people. The number of active social media users have more than doubled within a couple of years resulting in current record of over one billion. The lack of control of social media have created room for vices, such as fraud, falsehood, sedition, blackmail, pornography, invasion of privacy, and other unacceptable practices. One of the greatest problems affecting social media is that it promotes superficial connection that can end up causing long term emotional and psychological problems. This study was undertaken to determine social media and cyber-crime among Abraka residents. A sample of three hundred (300) respondents were drawn from seven (7) different locations and zones in Abraka, using the simple random sampling technique. The descriptive survey research design was adopted and data was collected from the three hundred (300) questionnaires administered and in-depth interview conducted. Data from questionnaires were analysed using the Statistical Package for the Social Sciences (SPSS) version 21 in order to test the extent to which social media users are aware of the use of social media platforms in the perpetuation of cyber-crime. The results revealed that social media platforms such as Whatsapp, Facebook, Twitter, Youtube, Badoo, Instagram, BBM, etc have been used to perpetuate cyber-crime. On the basis of these findings, the study concluded that social media-aided cyber-crimes have significant effect on its users and that social media, with its positive impact, have brought serious threats to the society. Based on the findings, the study recommends the use of password codes among social media users in order to restrict leakage of vital/relevant information on the internet from social media users to fraudsters.